A faithful gathering - Gould, Leslie, 1962- (The sisters of Lancaster county, 2018)
Leisel Bachmann left her Amish roots and beloved sisters to pursue a career in medicine without a second thought. She has an Englisch boyfriend, Nick Jordan, and dreams of a new life--but those dreams come crashing down when her sister Marie is diagnosed with cancer. Soon nothing is going as she planned--not her state boards, not her first nursing job, and certainly not her relationship with Nick. As she becomes increasingly discouraged, her aunt shares the story of Leisel's grandfather during World War II and the struggle he faced between returning to Lancaster or being with the woman he loved. Peace and a vision for the future are difficult to find, and when Nick leaves Pennsylvania for a completely new life, Leisel is faced with impossible choices. Will she stay in Lancaster, close to her family and the traditions of her past? Or learn from her grandfather's story and embrace a life of love and service in an uncertain future?